The Role of Technology in the Utilization of Methods for Learning Aqidah Ahlak in Society 5.0 Era (Case Study for VIII A Students at Mts. Al-Isro' Batealit Jepara) - Amelia Septianingrum; Takhiqul Jannah; Ahmad Saefudin (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the influence of educational technology on the learning methods of Aqidah Akhlak with a case study in class VIII A MTs. Al-Isro' Batealit Jepara in the Society 5.0 era. It is an era where society is highly connected to technology. The research in this paper aims to investigate the impact on students and educators. The research uses a descriptive qualitative method with observation, interviews, and document analysis as data collection techniques. The research findings show that educational technology has made access to various sources of information related to moral beliefs easier and faster. It resulted in more interactive learning methods with online discussions and forums and provided opportunities for students to participate actively. However, it is essential to exercise caution and ensure careful supervision in the use of educational technology to prevent students from being exposed to inappropriate content that might be inconsistent with religious values and morals. The research in this paper highlights the importance of emphasizing moral and ethical values in the learning process, even in the era of highly connected technology. In addition, the valuable insights on educators can optimize educational technology to improve students' religious understanding and practice.